Popliteal Artery Pseudoaneurysm after Prolonged Stress Position - Karla E Moncayo; Jose M Dominguez (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2015)
A 56-year-old man with past medical history of hypertension on treatment with valsartan and left fibula fracture 15 years ago, presented with a 2-month history of paresthesia on the left lower limb after working many hours on a vineyard in a squatting position. During the physical exam, the patient presented symmetric pulses on all extremities and a palpable, pulsatile mass on the left popliteal fossa. CT scan showed a patent popliteal artery with a saccular aneurysm of 37 millimeters in diameter (Figure 1), which was confirmed intraoperatively (Figure 2). A popliteal-popliteal bypass was done with the left great saphenous vein through a posterior approach (Figure 3). Blood, arterial wall and thrombus cultures were negative. Pathology confirmed diagnosis of pseudoaneurysm and no malignant cells were present. At 12-month follow-up the patient is asymptomatic with good distal pulses and no signs of bypass restenosis on ultrasound. The incidence of popliteal artery aneurysm is 0.1-1% [1], while traumatic pseudoaneurysm represents 0-3.5% of all popliteal aneurysms.